Sistem Pendukung Keputusan Pemilihan Bibit Tanaman Karet Dengan Metode Profile Matching - Ardin Natalius Harefa; Fricles Ariwisa Sianturi (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
PT. Asri Jaya had difficulty in selecting the best rubber plant seeds, both for direct planting in the plantations and recommending them to be marketed to rubber plantation companies, because the types of rubber plant seeds in the company had many varieties and varied as well as different ages of seeds. -different such as BPM seeds, IRR seeds, IRC, rubber frame seeds, GT (Gondang Tapen), PB seeds (Prang Besar), and so on. The alternatives used in this research are types of rubber plant seeds, namely BPM seeds (Balai/Pusat Perkebunan Medan, IRR (Indonesian Rubber Research) rubber seeds), IRC rubber seeds (Institute Research of Ceylon), frame rubber seeds, GT rubber seeds (Gondang Tapen) and PB (Prang Besar) rubber seedlings. The criteria used in this study were umbrella shape, petiole position, petiole shape, leaf color, leaf shape, leaf bone, leaf thickness, stem height, and seedling age. which is built using the programming language used in making the system is PHP with MySQL database. To calculate the total value, it must first determine the percentage of core factore and secondary factore. In this case the core factore is determined with a percentage value of 60% considering the main factor is an the most dominant aspect or criteria for assessing the selection of rubber plant seeds, the percentage value is greater than the pe value the percentage for the secondary factor is 40%.